2018
DOI: 10.1063/1.5025178
|View full text |Cite
|
Sign up to set email alerts
|

GaN/AlGaN multiple quantum wells grown on transparent and conductive (-201)-oriented β-Ga2O3 substrate for UV vertical light emitting devices

Abstract: GaN/AlGaN multiple quantum wells (MQWs) are grown on a 2 01-oriented β-Ga2O3 substrate. The optical and structural characterizations of the MQW structure are compared with a similar structure grown on sapphire. Scanning transmission electron microscopy and atomic force microscopy images show that the MQW structure exhibits higher crystalline quality of welldefined quantum wells, when compared to a similar structure grown on sapphire. X-ray diffraction rocking curve and photoluminescence excitation analyses con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 46 publications
3
40
0
Order By: Relevance
“…As can be seen from the TRPL measurements, in the longer wavelength (500−510 nm) range (related peak with a dominant intensity is centered at 506 nm), the carrier PL lifetimes exhibit a slow mono-exponential decay. Based on the rate equation, this slower single exponential suggests high radiative recombination rate, which concurs with the high PL intensity and is in line with the results obtained in previous studies [29][30][31][32] . On the other hand, in the shorter wavelength (450−490 nm) range, the carrier lifetimes exhibit faster bi-exponential decay, due to the presence of multiple centers resulting from different states.…”
Section: Resultssupporting
confidence: 91%
“…As can be seen from the TRPL measurements, in the longer wavelength (500−510 nm) range (related peak with a dominant intensity is centered at 506 nm), the carrier PL lifetimes exhibit a slow mono-exponential decay. Based on the rate equation, this slower single exponential suggests high radiative recombination rate, which concurs with the high PL intensity and is in line with the results obtained in previous studies [29][30][31][32] . On the other hand, in the shorter wavelength (450−490 nm) range, the carrier lifetimes exhibit faster bi-exponential decay, due to the presence of multiple centers resulting from different states.…”
Section: Resultssupporting
confidence: 91%
“…TRPL results indicated that the total lifetime was dominated by the slow decay component, which is indicative of highquality materials. Based on the available literature, the fast decay component is dominant in materials characterized by low crystal quality, [53,54] as it has been attributed to hot carrier−phonon interactions and optical phonon decay.…”
Section: Advanced Optical Analysis and The Band Structurementioning
confidence: 99%
“…To understand such carrier lifetime behavior in both materials, radiative and non-radiative components were analyzed, [51,54,55] and the results are reported in Figure 3e,f. As shown in Figure 3d, the lifetime of CsPbBr 3 at RT was dominated by radiative recombination (as it is in the same ns range of the total lifetime).…”
Section: Advanced Optical Analysis and The Band Structurementioning
confidence: 99%
“…Further advances in the field of DUV optoelectronics are hindered by other issues, such as the difficulty in developing new cost‐effective material production and fabrication methods that could replace the expensive and high vacuum‐based technologies presently in use. Thus, as DUV‐WBGS based devices tend to be prohibitively expensive, they are difficult to produce on a large scale . Moreover, the defects in the interface between layers, such as lattice mismatch and dislocation defects, significantly hinder the performance of DUV devices .…”
mentioning
confidence: 99%